Investigating the effect of powder recoater blade material on the mechanical properties of parts manufactured using a powder-bed fusion process. (September 2022) - Fox, Haley; Kamaraj, Abishek B.; Drake, Dana
Abstract: As additive manufacturing (AM) technology grows, more industries are learning how to utilize it for their specific applications. Powder bed fusion-based AM processes such as Direct metal laser solidification (DMLS) allow manufacturers to design more intricate or lightweight parts that could not be made with traditional tools. DMLS expands the capabilities of manufacturing, but the recoater blade that spreads powder presents challenges in printing delicate details such as lattice structures and high aspect ratio features. Hard steel or ceramic blades are often used to compact powder to create smooth, even layers that result in higher strength values of parts. However, small structures can be damaged by these blade types. Alternatively, a softer rubber or carbon fiber brush can be used to make the printing process easier by not breaking the small, printed features. On the other hand, parts made with softer blades are expected to have less strength and more defects. To compare the mechanical properties of finished parts due to blade type, 3 blade materials, high-speed steel (HSS), silicone rubber, and carbon fiber brush, were compared in this study. Tensile bars, cubes, and Voronoi lattice structure pucks were printed and analyzed for tensile properties, optical density analysis, as well as compression strength or toughness. These tests are often completed by original equipment manufacturers (OEM's) in the AM industry to qualify the machine's process. There were no significant tensile strength differences noticed of parts based on blade type and the values were all within the tolerance of OEM specifications. Optical density analysis indicated that the rubber blade builds have a higher number of large defects, greater than 75 μ m, and the brush blade has a higher number of small defects, less than 75 μ m in size. The HSS blade has zero defects greater than 90 μ m. There was no significant difference in maximum compression strength for the three blades, but the HSS blade produces parts with a standard deviation of toughness that is half of the other two blades. Inconsistencies shown in the soft blade builds may be due to the nature of the soft blades wearing faster over time during each build, however, the soft recoater blades can be a useful option if the application allows for occasional inconsistency.